Low prevalence of human pegivirus 1 (HPgV-1) in HTLV-1 carriers from Bel?m, Par?, North Region of Brazil - Lima, Ana Beatriz Figueiredo de (Public Library of Science, 2020)
Introduction - Human pegivirus 1 (HPgV-1) is a single-stranded, positive-sense RNA virus belonging to the Flaviviridae family with limited cause-effect evidence of the causation of human diseases. However, studies have shown a potential beneficial impact of HPgV-1 coinfection in HIV disease progression. Human T lymphotropic virus-1 (HTLV-1) is a retrovirus known for causing diseases, especially in muscle and white blood cells, in approximately 5% of patients. Thus, this study aimed to investigate the potential effects of an HPgV-1 infection in patients carrying HTLV-1 in the state of Par? in the North Region of Brazil. Methods - A group of HTLV-1 carriers was compared to healthy controls. Blood samples were collected, data from medical regards were collected, and a questionnaire was administered. HPgV-1 and HTLV-1 positivity was determined by quantitative polymerase chain reaction (qRT-PCR). The data were analyzed to correlate the effects of HPgV-1 coinfection in HTLV-1 carriers. Results - A total of 158 samples were included in the study: 74 HTLV-1-positive patients (46,8%) and 84 healthy controls (53,2%). The overall HPgV-1 positivity rate was 7.6% (12/158), resulting in a prevalence of 5.4% (4/74) and 9.5% (8/84) in HTLV-1 carriers and healthy controls, respectively. No significant differences were found when comparing any clinical or demographic data between groups. Conclusion - This study indicated that the prevalence of HPgV-1 infection is low in HTLV-1 carriers in Bel?m, Par?, and probably does not alter the clinical course of HTLV-1 infection, however, further studies are still needed.